Association between Serum Thyroid Hormone Levels and Functional Outcome in Acute Ischemic Stroke Patients (Bangladesh Journal of Neuroscience, 2018)
Background and Objectives: Neuroendocrine profile is significantly altered in acute ischemic stroke. Objective of the study was to determine association between serum thyroid hormone levels and functional outcome in acute ischemic stroke patients.Method: It was a cross sectional analytical study which was conducted in the Department of Neurology, BSMMU, Dhaka. Total 60 acute ischemic stroke patients within 14 days of onset of symptoms confirmed by neuroimaging were selected purposively from department of Neurology, BSMMU. Blood sample was collected from the patient on admission, and was analyzed at the Department of Biochemistry, BSMMU for estimation of serum Thyroid hormones (FT3, FT4, TSH) level. Modified Rankin Scale (mRS) score was done after 1 month of stroke. Poor outcome was defined as mRS>2 and good outcome was defined as 0-2.Result: Among Sixty patients 39(65%) had normal FT3 level and rest 21(35%) had low FT3 level.The mean (± SD) serum FT3 Level was 2.77 (±0.99) pmol/L in poor outcome group and 3.67 (±0.65) pmol/L in good outcome group which was statistically significant (p=0.001).A negative correlation co-efficient (r = - 0.380) was found between mRS score and serum FT3 concentration,which was also statistically significant (p=0.001).On logistic regression analysis, low serum FT3 concentration remained independent predictor of poor outcome of acute ischemic stroke patients (p=0.001, Odds Ratio = 3.567).Conclusion: In patients with acute ischemic stroke lower serum FT3 level was significantly associated with poor functional outcome.Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 9-16